Achievement of resilience in urbanism: A prototype for a simulative methodology - Yasser ElSayed Fouda; Deena Mohamed ElKhazendar (Alexandria Engineering Journal, 2023)
In recent years, the popularity of resilience has become an appealing perspective on cities in both academic and policy discourse. As urban losses and challenges of cities and their communities associated with natural and man-made disasters continue to increase, the consideration of resilience in the planning for future urban areas is of vital significance. Most of the literature reviews have failed to address resilience design principles that could be further used as an implementation method in urban planning. To develop better links between urban resilience theory and practice, and to help in closing the implementation gap; this paper develops a resilient prototype model for future growing cities (new urban formation) to sustainably function before disaster, and to adapt during/after emergency situations. The model is constructed by incorporating resiliency-related strategies including biodiversity, networks, multifunctionality, modularization and adaptive design, into the planning process. It also aims to develop integral uncertainty-oriented design solutions that cover all vulnerable facilities needed by the communities to provide both, physical and social resiliency. This is done by adopting the main resilience instrumental components during the formation of the model. Testing the prototype model for its abilities revealed its aimed characteristics to be robust, redundant, flexible, reflective, resourceful, inclusive, and integrated.